The divergence in demographic factors of Technical and Vocational Education (TVE) teacher commitment - Ahmad, Putri Asnorsalbiah; Ismail, Normala; Mustakim, Siti Salina (Human Resource Management Academic Research Society, 2022)
Teacher commitment is needed for the development and sustainability of the national education system. Therefore, the purpose of this study is to determine the level of TVE teachers’ commitment and to differentiate it based on gender, marital status, and level of education. Plus, the study also identifies the relationship of TVE teachers’ commitment with the selected demographic factor. The sample included 130 secondary school TVE teachers. Gender, marital status, age, years of service, and level of education were the demographic factors that this study focused on. For teacher commitment, the instrument used is a 16-item of 5-point Likert scale Teacher Commitment Scale with four dimensions. Respondents filled out an online survey using a Google Form. The data were analyzed by following descriptive and inferential statistics with SPSS version 25. The result showed that TVE teacher commitment is at a high level and there is no difference in TVE teacher commitment with gender, marital status, and level of education. However, there is a weak and significant relationship between TVE teacher commitment and marital status. As a result of the study, the researcher encourages policymakers to take measures to sustain the level of commitment of TVE teachers.